INTERNAL FACTOR RELATIONSHIP STUDENT WITH YIELDING LEARNED COHERENT IPS CLASS VII SMP N 20 MOORLANDS - Yolanda, Fitri; Suarto, Edi; Zahara, Leni (STKIP PGRI Sumbar, 2013)
This research intent for process, analyze, and working through about students internal factor with yielding learned coherent IPS class VII SMP n 20 Moorlands. This observational type is descriptive korelasional. Population in observational it is student brazes VII one be at SMP n 20 Moorlands that total 325 students.Â Observational sample to be taken by tech Random is Sampling Â with sample amount 76 students. Found observational result that: 1 )available relationship among motivates by IPSS studying result coherent student brazes VII SMPNS student 20 Moorlands since t computing > t table (2,973> 1,665), included subjective force category contemns (r = 0,327) and weeny contribution (10,7%), (2 ) available relationships among give a damn by IPSS studying result coherent class VII SMP n 20 Moorlands since t computings> t table (2,710> 1,665). Included subjective force low (r = 0,301) and weeny contribution (9,0%), (3 ) available relationships among student discipline with yielding learned coherent IPS class VII SMP n 20 Moorlands since t computings> t table (6,582> 1,665), included subjective force category be (r = 0,608) and outgrows it sizeable contribution (36,9%) and (4 ) available relationship which signifikan among motivates student, yen, ala student discipline in company with IPSS studying result coherent class VII SMP n 20 Moorlands since f computings> F table (22,541> 2,751). Subjective force among drd variable with IPSS learned result coherent class VII SMP n 20 Moorland comprises categories be (r = 0,696), meanwhile outgrows it contribution comprises sizeable (48,8%).Â